1990
DOI: 10.1038/ki.1990.19
|View full text |Cite
|
Sign up to set email alerts
|

Aortic and large artery compliance in end-stage renal failure

Abstract: Pulse wave velocity (PWV) was measured in the aorta, right leg and arm of 90 control subjects (CS) and 92 hemodialysis patients (HD) of the same age and mean arterial pressure (MAP). Blood chemistry, including blood lipids, and echographic dimensions of the aorta, were measured in all subjects. Presence of aortic calcification was evaluated by abdominal X-ray and echography. Whereas femoral and brachial PWV were only slightly increased in HD (P less than 0.05), the aortic PWV was significantly elevated (1113 +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
205
2
4

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 354 publications
(224 citation statements)
references
References 20 publications
13
205
2
4
Order By: Relevance
“…Several studies have shown that modifications of the vessel wall properties are common in haemodialysis patients and after renal transplantation. [5][6][7][8] . In renal transplant recipients, arterial distensibility of large arteries is reduced and the impaired arterial buffering capacity seems to contribute to cardiovascular morbidity after renal transplantation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that modifications of the vessel wall properties are common in haemodialysis patients and after renal transplantation. [5][6][7][8] . In renal transplant recipients, arterial distensibility of large arteries is reduced and the impaired arterial buffering capacity seems to contribute to cardiovascular morbidity after renal transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Structural and mechanical properties of the arterial wall are altered in patients with renal failure. [5][6][7][8] It has been shown that the distensibility of large arteries is reduced in haemodialysis patients and in renal transplant recipients. [6][7][8] Moreover it had been demonstrated that intima-media-thickness is increased in end-stage renal failure and is related to the mechanical properties of the arterial wall.…”
Section: Introductionmentioning
confidence: 99%
“…Arterial enlargement is a process associated with supposedly normal aging 32 but has also been associated with pathological conditions, such as hypertension in menopausal women, 33 hypertension, 34,35 CKD, 6 and end-stage renal disease patients. 36 In hypertensive patients, an increase in aortic diameter has been independently associated with target organ damage, such as cardiac hypertrophy. The reason why arterial dilation might predispose to premature death is still poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Increased PWV (indicating increased arterial stiffness) has been associated with increasing age, arterial blood pressure, 2 diabetes, 3 smoking, 4 and endstage renal disease. 5 Emerging evidence has also suggested an association between increasing arterial stiffness (as measured by PWV) and cardiovascular mortality. 6,7 Coexistent raised arterial blood pressure in diabetes is associated with increased cardiovascular morbidity and mortality.…”
mentioning
confidence: 99%